2022
DOI: 10.3390/ijms23094671
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Inheritance: Intergenerational Effects of Pesticides and Other Endocrine Disruptors on Cancer Development

Abstract: Parental environmental experiences affect disease susceptibility in the progeny through epigenetic inheritance. Pesticides are substances or mixtures of chemicals—some of which are persistent environmental pollutants—that are used to control pests. This review explores the evidence linking parental exposure to pesticides and endocrine disruptors to intergenerational and transgenerational susceptibility of cancer in population studies and animal models. We also discuss the impact of pesticides and other endocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Considering the protective effect of antioxidants against cancer and the pro-tumor effects of TNF- α , this scenario represents a disbalance that can stimulate cell proliferation, DNA damage, and immune deregulation, favoring BC development. It is important to highlight that pesticides, including those reported here in our study area, are pointed out as endocrine disruptors ( 43 46 ), an event intrinsically linked to deregulated immunological and inflammatory responses ( 9 ) that could confer some carcinogenic potential to such substances. Our findings strengthen several worldwide studies demonstrating augmented breast cancer risk in pesticide occupationally exposed women ( 47 55 ) by adding information about possibly implicated mechanisms in the pre-carcinogenic stages.…”
Section: Discussionmentioning
confidence: 90%
“…Considering the protective effect of antioxidants against cancer and the pro-tumor effects of TNF- α , this scenario represents a disbalance that can stimulate cell proliferation, DNA damage, and immune deregulation, favoring BC development. It is important to highlight that pesticides, including those reported here in our study area, are pointed out as endocrine disruptors ( 43 46 ), an event intrinsically linked to deregulated immunological and inflammatory responses ( 9 ) that could confer some carcinogenic potential to such substances. Our findings strengthen several worldwide studies demonstrating augmented breast cancer risk in pesticide occupationally exposed women ( 47 55 ) by adding information about possibly implicated mechanisms in the pre-carcinogenic stages.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, although the risks of pesticide exposure have been vastly evaluated, the transgenerational effects of these exposures need more attention. It has been shown that the environmentally induced disease risk can be transmitted to the offspring, via epigenetic mechanisms through female and male germ lines [ 199 ].…”
Section: Discussionmentioning
confidence: 99%
“…While life-style factors such as obesity have been shown to alter sperm non-coding RNAs in men, 53 no human studies have directly investigated the link between environmental toxicants such as DDT and germline RNA changes to the best of our knowledge; though several reports in animal models exist. [54][55][56] Nonetheless, a number of epidemiological studies link parental environmental toxins and cancer in the progeny. For instance, an association between paternal exposure to pesticides and a number of childhood cancers in offspring has been reported.…”
Section: Discussionmentioning
confidence: 99%